THE EFFECTS OF ANTENATAL PELVIC FLOOR MUSCLES EXERCISES ON THE LENGTH OF THE SECOND STAGE OF LABOR AMONG PRIMIGRAVIDA WOMEN ATTENDING SULAIMANI MATERNITY TEACHING HOSPITALS FOR DELIVERY - HosseinAli, Shaghayegh HamidReza; Mohammed, Atiya K. (Journal of Sulaimani Medical College, 2021)
Background The role of pelvic floor muscle training in decreasing urinary incontinence problems is well established but its effects on labor and newborn outcomes need more study. Objectives To evaluate the effect of pelvic floor muscle exercises on the length of the second stage of labor among primigravida women. Methods This is a quasi-experimental study done from February to November 2019, which recruited 160 Primigravida Women aged between 18-35-year-old and matched the inclusion criteria. The participants were qualified and included in the study with 18 weeks of gestational age. Thus study group started the training as 6 sessions of 2-hour training established and distributed through 20 weeks. Then, all participants were observed during labor by the researcher. Subsequently, the collected data got processed, and the experimental and the control group delivery outcomes got compared. Results Highly significant difference regarding education (70.0% of the study group had Institute-College degree while the rate in the control group was 39.0%), occupation (62.0% of the study group and 87.0% of the control group were housewives), economic status (80.0% of the study group were economically satisfied while this rate in the control group was 8.8.0%). There was a significant difference regarding the duration of the second stage of labor (p=0.05) and the third stage of labor (p=0.001), while there was a difference at the edge of significance (p=0.056) between both groups in the first stage of labor. Conclusion This quasi-experimental study found a significant effect of pelvic floor exercise on the length of the second stage of labor.
Keywords: Labor; Primigravida; Pelvic floor muscle training; The second stage of labor